2007
DOI: 10.1016/j.ijgo.2006.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Mifepristone and misoprostol in the induction of labor at term

Abstract: In this pilot sample, 400 mg of mifepristone was effective in inducing cervical changes and labor. Although there were no adverse effects using oral misoprostol in combination with mifepristone, labor was more difficult to induce in the women who did not respond to mifepristone alone, and these women had a higher operative delivery rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 14 publications
2
20
0
Order By: Relevance
“…In our study, we observed that mifepristone is associated with favorable outcome in 89 % of women (labor onset in 56 % and cervical ripening 33 %) within 48 h of administration of oral mifepristone. These observations are in accordance with the existing literature where a variable success rate of labor onset at 66-93 % has been observed in pregnant women [8][9][10][11][12][13][14][15]. Also, the effect of cervical ripening after use of mifepristone has been variable ranging from no statistically difference to statistically significant improvement (60-80 % of all cases) [16][17][18][19][20].…”
Section: Discussionsupporting
confidence: 90%
“…In our study, we observed that mifepristone is associated with favorable outcome in 89 % of women (labor onset in 56 % and cervical ripening 33 %) within 48 h of administration of oral mifepristone. These observations are in accordance with the existing literature where a variable success rate of labor onset at 66-93 % has been observed in pregnant women [8][9][10][11][12][13][14][15]. Also, the effect of cervical ripening after use of mifepristone has been variable ranging from no statistically difference to statistically significant improvement (60-80 % of all cases) [16][17][18][19][20].…”
Section: Discussionsupporting
confidence: 90%
“…Remaining 68% Women required Misoprostol for induction of labor .Out of that 56% delivered virginally, which quite low compare to study is done by Li L 10 who found 80% delivered vaginally.44% required cesarean section. J. Mcgill 11 found rate of cesarean section was higher in women who required T. Mifeprostol followed by T. Misoprostol.…”
Section: Discussionmentioning
confidence: 98%
“…J McGill et al 11 found 66% women went in labor without T. Misoprostol. Elliot CL et al 7 found in their conclusion that T. Mifeprostol is known to cause softening and dilatation of cervix and increase in uterine activity.…”
Section: Discussionmentioning
confidence: 98%
“…According to various existing literature, the labor onset and cervical ripening observed. [8][9][10][11][12] There is need of oxytocin requirement for augmentation of labour is very minimum so there is very less chances of scar dehiscence and rupture uterus. Mifepristone initiate the labour as naturally, causes cervical ripening (by releasing NO),promote uterine contractions by forming gap junctions and increasing influx of calcium it also increases the prostaglandins release without acting as a direct uterotonic.…”
Section: Discussionmentioning
confidence: 99%